RIVER FUNCTIONING ANALYSIS FROM SUSPENDED SEDIMENT AND WATER DISCHARGE STUDY: THE CASE OF THE IVAÍ RIVER, SOUTHERN BRAZIL - Leli, Isabel Terezinha; Stevaux, José Cândido; Cremon, Édipo Henrique; da Nóbrega, Maria Tereza (Revista Brasileira de Geomorfologia, 2017)
This paper presents the spatial distribution of liquid and solid (suspended load) discharge in the Ivaí River Basin, and its implication in the functioning of this river system. The Ivaí is a typical medium-size river of the basaltic plateau, the left side of the Paraná River Basin in southern Brazil. The data relating to water discharge and concentration of suspended sediment come from 19 gauging stations controlled by the former Superintendence of Water Resources and Environmental Sanitation Development – SUDERHSA, today Water Institute of Paraná. The river drains an area of 36,587 km2, and its average discharge during the study period (1974–2008) was 702.9 m3 s-1. The specific discharge (Qsp = Qm:Ab) varied uniformly between 0.01 and 0.02 m3 s-1 km2, however, an anomalous result of 0.11 m3 s-1 km2 was identified. Most of the water that enters the Ivaí River comes from the smaller sub-basins (< 500 km2), and the specific discharge from the tributaries decreases from upstream to downstream, from 0.028 to 0.015 m3 s-1 km-2. Correlations are high between the annual production of suspended sediment versus average discharge (R2 = 0.97) for all river gauging stations, and the contribution of suspended load versus basin area (R2 = 0.95). The water and suspended sediment discharge of the Ivaí River is similar to those dry-wet, temperate climate river in the world. A good correlation was also obtained when the river was compared with others plateau river in the world. The results make a great contribution to the management and planning projects for many basaltic-plateau rivers along the eastern side of the upper Paraná Basin, Brazil.